2011
DOI: 10.1001/archdermatol.2011.50
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of Odontogenic Keratocysts of the Jaw in Basal Cell Nevus Syndrome With GDC-0449

Abstract: Background: Odontogenic keratocysts of the jaw are a central feature of basal cell nevus syndrome (BCNS) and arise from the basal cell layer of the surface epithelium. Although they are benign, they tend to be aggressive, with local invasion of bony structures, extensive growth, and potential for substantial disfigurement and speech dysfunction. Complete surgical resection is the current standard of care; however, the procedures are often technically challenging and are followed by high recurrence rates.Observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 5 publications
0
34
0
2
Order By: Relevance
“…, 100 101 Gastric epithelial stem cells may be the cellular origin of gastric cancer. 102,103 Under mucosal injury and inflammation, mature gastric chief cells act as cryptic progenitors and reacquire the ability of proliferation. 104 Study of Hh signaling in gastric cancer stem cells has just begun.…”
Section: Hh Signaling In Gastroesophageal Cancer Stem Cellsmentioning
confidence: 99%
“…, 100 101 Gastric epithelial stem cells may be the cellular origin of gastric cancer. 102,103 Under mucosal injury and inflammation, mature gastric chief cells act as cryptic progenitors and reacquire the ability of proliferation. 104 Study of Hh signaling in gastric cancer stem cells has just begun.…”
Section: Hh Signaling In Gastroesophageal Cancer Stem Cellsmentioning
confidence: 99%
“…Another hypothesis is that higher doses of vismodegib are required to induce shrinkage. Indeed, the dose used in our study was almost half of that used in Goldberg et al’ s case report 3 and, cyclopamine (another HH pathway inhibitor) has been found to significantly arrest the growth of KCOT cells in a dose-dependent manner in vitro 10 . However, since all our patients received the same FDA-approved dose of vismodegib, we were not able to assess any dose-dependent response.…”
Section: Discussionmentioning
confidence: 73%
“…In one case report, Goldberg et al 3 incidentally noted resolution of KCOTs in one BCNS patient treated with vismodegib (270mg/day) for 2 years. This dose was used in phase 1-studies before the data demonstrated 150mg/day to be the most efficacious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, palmoplantar pits of BCNS disappeared during vismodegib treatment. In addition, vismodegib treatment reduced the size of odontogenic cysts by at least 50% from baseline and could represent an alternative to surgery for some patients (52).…”
Section: Preclinical Efficacy Modelsmentioning
confidence: 99%